Pengaruh Profitabilitas,Ukuran Perusahaan dan Kepemilikan Manajerial Terhadap Earning Management Pada Perusahaan Manufaktur Sub Makanan dan Minuman yang terdaftar di BEI Tahun 2019-2022: Profitabilitas,Ukuran Perusahaan dan Kepemilikan Manajerial dan Manajemen Laba - Madrawan, Gede Rendy; I Gede Agus Pertama Yudantara (Vokasi : Jurnal Riset Akuntansi, 2024)
This research aims to determine the influence of Profitability, Company Size, Managerial Ownership, on Profit Management. The population in this study were 26 sub-food and beverage manufacturing companies. In this research, the sampling technique used was purposive sampling so that a sample of 17 companies was obtained during 4 years of observation for a total of 68 data. The data source used in this research is secondary data obtained from annual report data and company financial reports. multiple linear regression analysis. In this research, the data was processed using the SPSS version 21 for Windows program. The research results show that: (1) profitability has a positive and significant effect on earnings management with a sig value of 0.000 < 0.05. (2) Company size has no significant effect on earnings management with a sig value of 0.071 > 0.05. (3) managerial ownership has no significant effect on earnings management with a sig value of 0.143 > 0.05.